Present time tracker / Mohd Fuad Abdul Latip … [et al.] - Abdul Latip, Mohd Fuad; Taib, Mohd Nasir; Binti Mohamad Zaini, Norliza; Noor, Mohd Zikrul Hakim; Alimon, Sadiyah (Research Innovation Business Unit, 2014)
Present Time Tracker (PPT) is a system to record the arrival of staff online. The system provides many benefits to staff and the management. These systems provide space for staff to check in from any wifi –connected gadgets such as smart phones, tablets and other devices that can access the internet. The system facilitates staff to not have to move to the conventional punch card machine terminal which may delay them. Staff can also see the arrival time in order to plan activities effectively. In addition, the system provides many benefits to management where management can see real-time attendance record of staff members. With this the management can monitor the presence of staff. In addition, the system provides facilities for management to keep staff report each month to the coming of university records. The system also features all staff profile that can be updated by the staff. The system will also provide the latest news and information from the management to staff members.